Erratum: SHREYAS BETAGERI, VANAJA G. PATGAR& K. KOTRESHA (2025)Parasopubia gorensis (Orobanchaceae): A new species from Uttara Kannada, Karnataka, India. Phytotaxa 708 (3): 281–286. - Betageri, Shreyas; Patgar, Vanaja G.; Kotresha, K. (Phytotaxa, 2025)
N/A